2021
DOI: 10.1002/jnr.24807
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte‐induced synapse formation and ischemic stroke

Abstract: Astrocytes envelop synapses and blood vessels with their cellular projections, regulate their functions, and mediate varied effects in response to brain damage such as stroke (Gleichman & Carmichael, 2014). For example, astrocytes promote synaptic structure formation during the wrapping of dendritic spines and presynaptic terminals (Haber et al., 2006; Theodosis et al., 2008). In addition, changes in the structural relationships between astrocytic processes and dendritic spines regulate synaptic plasticity (Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 127 publications
(225 reference statements)
0
17
0
Order By: Relevance
“…Evidence of the relationship between ischemic brain injury and increased astrocyte injury has been found in previous research. 16 Astrocytes are the most abundant cell type in the central nervous system. 17 They communicate with neurons, oligodendrocytes and endothelial cells, and participate in maintaining normal brain function.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of the relationship between ischemic brain injury and increased astrocyte injury has been found in previous research. 16 Astrocytes are the most abundant cell type in the central nervous system. 17 They communicate with neurons, oligodendrocytes and endothelial cells, and participate in maintaining normal brain function.…”
Section: Discussionmentioning
confidence: 99%
“…Glial cell-derived cholesterol serves as a raw material for synaptogenesis, promotes synaptogenesis and regulates myelin formation after stroke (149). Studies have reported that various molecules secreted by glial cells, such as TNF-a, thrombospondin, hevin have the ability to repair synaptic dysfunction after stroke (150). Beyond that, microglia and astrocytes secrete various nutrients and growth factors such as BDNF, nerve growth factor (NGF), and basic fibroblast growth factor (bFGF), which are useful for neural repair and plasticity (151,152).…”
Section: Glial Cell-related Neural Repair After Strokementioning
confidence: 99%
“…Astrocytes, one of the glial cells, modulate synapse formation and synaptic transmission in the CNS [44][45][46]. TSPs are a component of the intercellular signaling network mediated by astrocytes in the CNS [47,48], and astrocyte-derived TSPs are considered an essential synaptogenic signal in synaptogenesis [31,[48][49][50].…”
Section: Relationships Of Tsps With the Nervous Systemmentioning
confidence: 99%